A finite element analysis on combined convection and conduction in a channel with a thick walled cavity - Rahman, M. M.; Öztop, Hakan Fehmi; Mekhilef, S.; Saidur, R.; Chamkha, A.; Ahsan, A.; Al-Salem, Khaled S. (Emerald Group Publishing Ltd, 2014)
Purpose - The purpose of this paper is to examine the effects of thick wall parameters of a cavity on combined convection in a channel. In other words, conjugate heat transfer is solved. Design/methodology/approach - Galerkin weighted residual finite element method is used to solve the governing equations of mixed convection. Findings - The streamlines, isotherms, local and average Nusselt numbers are obtained and presented for different parameters. It is found heat transfer is an increasing function of dimensionless thermal conductivity ratio. Originality/value - The literature does not have mixed convection and conjugate heat transfer problem in a channel with thick walled cavity.
Keywords: Combined convection; Conjugate heat transfer; Nonlinear; Open channel